Contagion - Bowman, Erin (HarperTeen, 2019)
When a distress call is received from a drill team on a distant planet, a skeleton crew is sent to perform what is assumed will be a standard search-and-rescue mission. But when they arrive, the team finds the planet littered with the bodies of the drill team and the wreckage of the project. As the rescue team tries to piece together what happened, they discover that some things are best left buried.